Dinamika Populasi Mikroorganisme Yang Berperan Dalam Transformasi Nitrogen Di Beberapa Jenis Tanah Akibat Perlakuan Paraquat - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT The effect of paraquat on population dynamics of microorganisms that are responsible to nitrogen transformation and the difference of that microorganisms responses in some soils were studied. This study used Complete Randomized Design with 3 kinds of soil, peat (extraordinary acid, high organic matter & low clay contain), andisol (very strong acid, moderate organic matter & moderate clay contain)/ and alfisol (moderate acid, low organic matter & high clay contain) with and without 20 ppm of paraquat, and it was used 3 replications. Soils were incubated within 8 weeks and the populations of microorganism were observed every 2 weeks. Data were statitically and analyzed using analysis Variant and Durtcan's Multiple Range Test. During 8 weeks incubation, 20 ppm of paraquat in peat increased the population of microorganisms that are capable in oxidizing nitrite to nitrate. The population dynamics of microorganisms that are responsible to nitrogen transformation in andisol and alfisol were not influenced by the addition of paraquat. There was difference effect of paraquat on population dynamics of microorganisms that are capable to oxidizing nitrite to nitrate in peat and both andisol and alfisol. Keywords : microbial vovulation, soils and varaauat